Rethinking interdisciplinarity across the social sciences and neurosciences (2015)
In the introduction, we introduce our monograph, Rethinking Interdisciplinarity, as a report from the interdisciplinary field – and an account of our own attempts to work and live across the social sciences and neurosciences. The introduction sets out the core goal of the volume, which is to give a sense, beyond bland encouragements, of what actually goes into, and what goes on in, interdisciplinary projects. The introduction sets out the core reasons that we have pursued interdisciplinary research, with our collaborators, across the neurosciences and social sciences – but it also establishes our view that interdisciplinarity is nonetheless a problem, or a set of problems, to be analysed in its own right.